2005
DOI: 10.1051/vetres:2005014
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between the isolation of Salmonella from mesenteric lymph nodes and the results of serological screening in slaughter pigs

Abstract: -Most Salmonella control programmes are based on serological testing in the slaughterhouse. However, from a point of view of carcass contamination, it is rather the presence of Salmonella spp. in the animal at the time of slaughter that is important. The aim of this crosssectional study was to investigate the possible discrepancies between the isolation of Salmonella spp. in the mesenteric lymph nodes and the results of serological screening. In total, 1821 fattening pigs originating from 60 Belgian farrow-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 27 publications
3
43
1
1
Order By: Relevance
“…The calculation of discrepancies between the serological and the bacteriological results was not the aim of the present study, but has been described in a previous paper [24]. Those results showed that the correlation between both diagnostic tests was weak, particularly at the individual level, and that the serological reaction depended on the serotype isolated.…”
Section: Discussionmentioning
confidence: 63%
“…The calculation of discrepancies between the serological and the bacteriological results was not the aim of the present study, but has been described in a previous paper [24]. Those results showed that the correlation between both diagnostic tests was weak, particularly at the individual level, and that the serological reaction depended on the serotype isolated.…”
Section: Discussionmentioning
confidence: 63%
“…The difference with observational studies [8,24], which showed discrepancies between seropositive and shedding prevalences, could be reduced by taking into account the sensitivity of the detection tests.…”
Section: Discussionmentioning
confidence: 82%
“…First, the serological status at primary production is converted to internal infection status after transport & lairage with an animal being assumed to be internally contaminated if the mesenteric lymph node (MLN) sample is positive (carrier pig) and/or if the colon content (CC) is positive (excreting pig). The corresponding conditional probabilities could be derived using data from two Belgian studies [24], [25]. Second, the internal infection status of a pig is converted to external contamination status.…”
Section: Composition Meat MIXmentioning
confidence: 99%
“…In a first Belgian study, conducted by Nollet et al [24], the association between the results from serological screening (indirect ELISA, threshold value ζ = 0.25) and the isolation of Salmonella from MLN at slaughterhouse is investigated. In this study, 60 Belgian herds were sampled at four different slaughterhouses.…”
Section: Internal Infectionmentioning
confidence: 99%